Effects of family ownership and management on small business equity financing - Wu, Zhenyu; Chua, Jess H.; Chrisman, James J. (Journal of Business Venturing, 2007)
Equity financing is important in financing growth but its special features in small business have not been well addressed in the finance or entrepreneurship literature. Since many small firms have family involvement and research shows that family firms have both advantages and disadvantages in managing agency costs, how family involvement and agency issues interact to affect equity financing in small business is an important topic of research. This study examines the effects of family ownership and management on two dimensions of small business equity financing, the use of equity financing and the use of public equity financing within the agency theory of financing. The results show that family involvement and agency issues interactively and separately influence equity financing in small business.